Molecular tests for human papillomavirus (HPV), Chlamydia trachomatis and Neisseria gonorrhoeae in liquid-based cytology specimen - Lee, Sin Hang (BioMed Central, 2009)
BACKGROUND: Laboratory detection of Human papillomavirus (HPV), Chlamydia trachomatis and Neisseria gonorrhoeae in liquid-based cervicovaginal cytology specimens is now based on identification of the DNA sequences unique to these infectious agents. However, current commercial test kits rely on nucleotide probe hybridization to determine DNA sequences, which may lead to diagnostic errors due to cross-reactivity. The aim of this study was to find a practical approach to perform automated Sanger DNA sequencing in clinical laboratories for validation of the DNA tests for these three infectious agents. METHODS: A crude proteinase K digestate of 5% of the cells collected in a liquid-based cervicovaginal cytology specimen was used for the detection of DNA molecules specific for HPV, C trachomatis and N gonorrhoeae, and for preparation of materials suitable for direct automated DNA sequencing. Several sets of commercially available polymerase chain reaction (PCR) primers were used to prepare nested PCR amplicons for direct DNA sequencing. RESULTS: Some variants of HPV-16 and HPV-31 were found to share an at least 34-base long sequence homology downstream of the GP5+ binding site, and all HPV-6 and HPV-11 variants shared an upstream 34-base sequence including part of the GP5+ primer. Accurate HPV genotyping frequently required more than 34-bases for sequence alignments to distinguish some of the HPV genotype variants with closely related sequences in this L1 gene hypervariable region. Using the automated Sanger DNA sequencing method for parallel comparative studies on split samples and to retest the residues of samples previously tested positive for C trachomatis and/or for N gonorrhoeae, we also found false-negative and false-positive results as reported by two commercial nucleic acid test kits. CONCLUSION: Identification of a signature DNA sequence by the automated Sanger method is useful for validation of HPV genotyping and for molecular testing of C trachomatis and N gonorrhoeae in liquid-based cervicovaginal Papanicolaou (Pap) cytology specimens for clinical laboratories with experience in molecular biology to increase the specificity of these DNA-based tests. However, even a highly specific test for high-risk HPV genotyping may have unacceptably low positive predictive values for precancer lesion in populations with a low cervical cancer prevalence rate.